The last bastion of the Syrian revolt: Southern Syria offers non-military venues to strengthen moderates - Khaled Yacoub Oweis (Stiftung Wissenschaft und Politik (SWP), 2015)
After almost four years of civil war, most of Syria since has been carved up between the regime, Kurdish militia and Jihadists, with the exception of the south, where civic organizations in areas outside regime control have room to operate and Western and Arab support has helped moderate rebels remain significant players. Yet, their position has become tenuous as the local al-Qaeda affiliate has taken the lead in fighting the Assad regime in the south and as the priority of the United States shifted to curbing hard-line Jihadists through airstrikes in Syria and Iraq. Saving the south as a model that could halt the disintegration of Syria would require a change in the ambivalent position of outside powers to help Western-backed rebels advance against the regime. Germany and other European countries doubtful of a military approach can still help open the region to more streamlined civilian support and shape a stalled UN ceasefire initiative focused on Aleppo to be tried in the south, where the military balance is less tilted toward Assad and the stakes are higher if breaches occur. (SWP Comments)
Keywords: 320